2021
DOI: 10.1111/age.13156
|View full text |Cite
|
Sign up to set email alerts
|

New insights into genetics underlying of plumage color

Abstract: Plumage color can be considered as a social signal in chickens and a breeding identification tool among breeders. The relationship between plumage color and trait groups of immunity, growth and fertility is still a controversial issue. This research aimed to determine the genome-wide additive and epistatic variants affecting plumage color variation in chickens using the chicken Illumina 60k high-density SNP array. Two scenarios of genome-wide additive association studies using all SNPs and independent SNPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 100 publications
1
13
0
Order By: Relevance
“…A previous study on Swainson's thrush (Catharus ustulatus) confirmed that relevant regions, including TYRP1, were selected during evolution [47]. The findings related to chicken feather color confirmed 18 potential candidate regions, including HNF4BETA, CKMT1B, TBC1D22A, RPL8, CACNA2D1, FZD4, SGMS1, IRF8, OPTN, LOC420362, TRABD, OVODA1, DAD1, USP6, RBM12B, miR-1772, miR-1709, and miR-6696; 89 gene-gene combinations that may lead to changes in feather color may be primarily responsible for chicken feather color [48]. Additionally, the diversity of MC1R was associated with plumage color in pigeons [49].…”
Section: Discussionmentioning
confidence: 87%
“…A previous study on Swainson's thrush (Catharus ustulatus) confirmed that relevant regions, including TYRP1, were selected during evolution [47]. The findings related to chicken feather color confirmed 18 potential candidate regions, including HNF4BETA, CKMT1B, TBC1D22A, RPL8, CACNA2D1, FZD4, SGMS1, IRF8, OPTN, LOC420362, TRABD, OVODA1, DAD1, USP6, RBM12B, miR-1772, miR-1709, and miR-6696; 89 gene-gene combinations that may lead to changes in feather color may be primarily responsible for chicken feather color [48]. Additionally, the diversity of MC1R was associated with plumage color in pigeons [49].…”
Section: Discussionmentioning
confidence: 87%
“…Also, we identified the FZD4 as a candidate gene, which is associated with the pattern of phenotypic variation of plumage color (white, mixed and brown) in chicken. Plumage color is an important qualitative trait that can serve as marker for breed identification and can be considered indirectly as an economically important trait that is under the influence of multiple genes, gene–gene interactions, and environmental factors [ 53 ]. Several local Northern breeds show a white (Bianca di Saluzzo, Polverara Bianca, Ermellinata di Rovigo) or brown plumage color (Bionda Piemontese, Robusta Lionata, Padovana Camosciata).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plumage colour is considered an indirect economic trait because consumers prefer specific plumage colours for religious or nutritional reasons. Specifically, pure black and white chickens are preferred for religious reasons in Chad and the black‐boned chickens, which also have black plumage, are favoured in China for their nutritional value (Bibi et al, 2021; Davoodi et al, 2022; Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plumage colour is considered an indirect economic trait because consumers prefer specific plumage colours for religious or nutritional reasons. Specifically, pure black and white chickens are preferred for religious reasons in Chad and the black-boned chickens, which also have black plumage, are favoured in China for their nutritional value (Bibi et al, 2021;Davoodi et al, 2022;Yu et al, 2017).In general, plumage colouration in birds serves a variety of functions such as camouflage or mimicry, interspecific communication, and protection from sunburns (Gomes et al, 2016;Prum, 2014;Rogalla et al, 2022). Plumage pigmentation exhibits various physiological and behavioural traits related to sexual selection and aids in the assessment of individual quality (Javůrková…”
mentioning
confidence: 99%
See 1 more Smart Citation